Guru Zuhri: Pelayan Bimbingan Islam di Bangka Belitung - Rozi, Rozi (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
This research is the result of studies and observations on the provision of Islamic guidance through group guidance services by Zuhri’s Teacher in Kayu Besi Village, Puding Besar District, Bangka Regency. This research is a field research. The main data collection is done through in-depth interviews, and is strengthened by participatory observation, accompanied by official and personal documentation. The results showed that the implementation of Zuhri Guru’s Islamic guidance included the purpose of implementing the guidance, functions, materials used, and principles agreed upon in it, as well as the benefits obtained by the guidance group members. Not only that, the success of the group guidance service they carried out was inseparable from the things that influenced the implementation of the guidance service, both positive and negative influences. This can be seen from the leaders of their groups, their group members and their economy.